ChemInform Abstract: The btp [2, 6‐Bis(1, 2, 3‐triazol‐4‐yl)pyridine] Binding Motif: A New Versatile Terdentate Ligand for Supramolecular and Coordination Chemistry. Issue 38 (10th September 2014) - Byrne, Joseph P.; Kitchen, Jonathan A.; Gunnlaugsson, Thorfinnur
Abstract Review: 164 refs.